Influence the of Na-LTA synthesis route on low-carnegieite crystallization and stability - Radulović Aleksandra M.; Dimitrijević Radovan Ž.; Vulić Predrag; Dondur Vera T. (Hemijska Industrija, 2007)
The thermal transformation of zeolite precursor is a relatively novel route for the synthesis of aluminosilicate-based ceramic materials which had found numerous uses in the production of dielectric ceramics, microelectronic packaging electromagnetic windows, high-temperature electrical insulators, glass ceramic materials, etc. The mechanism of a thermally induced transformation strongly depends on the extra framework cations and the type of used zeolites. The sodium form of LTA zeolite transforms to low-carnegieite (lt-Carn) in the temperature range between 800 and 900°C. The formed low-carnegieite transforms to nepheline at >900°C. However, the mechanisms of the thermal transformation of Na-LTA zeolite into the low-carnegieite (lt-Carn) phase are still not completely understood. Different structure transformation mechanisms of Na-LTA zeolite into lt-Carn heve been reported. The carnegieite can be formed by a direct solid-solid topotactic transformation: Na-LTA -> lt-Carn. A two step mechanism: Na-LTA -> Am -> lt-Carn can also take place. Such behavior is probably the consequence of the applied synthesis route in the precursor preparation. Therefore, it is of interest to consider the influence of the zeolite preparation route on the processes of thermal transformation of Na-LTA zeolite into lt-Carn. The present paper deals with a systematic study on the thermally induced phase transformation of sodium LTA zeolites synthesized by the gel route under different reaction conditionss. Different gel compositions Na2O(2.4-3.9):Al2O3(l):SiO2(1.5-2.0):H2O(90-170) were used and several zeolite samples were prepared. The prepared zeolite samples were thermally treated at different temperatures from 600 to 950°C at an interval of 20 °C and the products were analyzed by X-ray diffraction. The zeolites and formed products were characterized by various methods including XRPD, IR, DTA, SEM. It was shown that the rate of lt-Carn formation is dependent on the composition and conditions of gel preparation. It was determined by X-ray diffraction analysis that all the synthesized Na-LTA zeolites recrystallised into lt-Carn or a new crystalline intermediate phase. The amorphous phase was not present in the investigated system. The mechanism of the direct solid-solid topotactic transformation: Na-LTA -> lt-Carn was confirmed.